Different cadences and resistances in sub-maximal synchronous handcycling in able-bodied men: Effects on efficiency and force application - Kraaijenbrink, Cassandra; Vegter, Riemer J. K.; Hensen, Alexander H. R.; Wagner, Heiko; van der Woude, Lucas H. V. (PLOS ONE, 2017)
Background With the introduction of an add-on handcycle, a crank system that can be placed in front of a wheelchair, handcycling was made widely available for daily life. With it, people go into town more easily, e.g. to do groceries; meet up with friends, etc. They have more independency and can be socially active. Our aim is to explore some settings of the handcycle, so that it can be optimally used as a transportation device. Therefore, the effects of cadence and added resistance on gross mechanical efficiency and force application during sub-maximal synchronous handcycling were investigated. We hypothesized that a cadence of 52 rpm with a higher resistance (35 W) would lead to a higher gross mechanical efficiency and a more tangential force application than a higher cadence of 70 rpm and no extra resistance (15 W). Methods Twelve able-bodied men rode in an instrumented add-on handcycle on a motorized level treadmill at 1.94 m/s. They performed three sessions of three four-minute blocks of steady state exercise. Gear (70, 60 and 52 rpm) was changed in-between the blocks and resistance (rolling resistance +0 W, +10 W, +20 W) was changed across sessions, both in a counterbalanced order. 3D force production, oxygen uptake and heart rate were measured continuously. Gross mechanical efficiency (ME) and fraction of effective force (FEF) were calculated as main outcomes. The effects of cadence and resistance were analyzed using a repeated measures ANOVA (P<0.05) with Bonferroni-corrected post-hoc pairwise comparisons. Results With a decrease in cadence a slight increase in ME (70 rpm: 5.5 (0.2)%, 60 rpm: 5.7 (0.2)%, 52 rpm: 5.8 (0.2)%, P = 0.008, η2p = 0.38), while an increase in FEF (70 rpm: 58.0 (3.2)%, 60 rpm: 66.0 (2.8)%, 52 rpm: 71.3 (2.3)%, P<0.001, η2p = 0.79) is seen simultaneously. Also with an increase in resistance an increase in ME (+0 W: 4.0 (0.2)%, +10 W: 6.0 (0.3)%, +20 W: 7.0 (0.2)%, P<0.001, η2p = 0.92) and FEF (+0 W: 59.0 (2.9)%, +10 W: 66.1 (3.4)%, +20 W: 70.2 (2.4)%, P<0.001, η2p = 0.56) was found. Interpretation A cadence of 52 rpm against a higher resistance of about 35 W leads to a more optimal direction of forces and is more mechanically efficient than propelling at a higher cadence or lower resistance. Therefore, changing gears on a handcycle is important, and it is advised to keep the linear hand velocity relatively low for locomotion purposes.